A teologia ancorada no mundo da vida e dialogicamente situada na esfera pública: uma contribuição ao debate contemporâneo sobre teologia pública - Jacobsen, Eneida (2011)
This essay offers a panoramic study about the concepts of public theology and public sphere, especially concerning the Brazilian context. In the first chapter, different understandings of public theology are identified and classified according to models of substantiation and models of performance. Based on the North American and South African examples, it is argued that the conceptual diversity concerning the theme is a reflection of concerns that are specific to each context, meaning that it is possible to assume that a public theology in Brazil develops its own theoretical feature as well. In the second chapter, we describe three important concepts of public sphere present in the contemporary philosophical thought: the liberal, with representatives like John Rawls and Bruce Ackerman, the republican (and communitarian), represented by Hannah Arendt and Charles Taylor, and the discursive, especially developed by Jürgen Habermas. Habermasian theoretical reference is the most recurrent in sociological analysis about public sphere in Brazil, which is the theme of the third chapter. We seek to demonstrate that major social changes have contributed to the creation of a discursive public sphere, despite a strong patrimonial tradition that characterizes the country's political history. In the last chapter, in view of this context of democratic reconstruction, we present a brief outline of a model of public theology anchored in the world of life and guided by dialogue concepts explored, especially, on the basis of a discursive conception of public sphere and contributions from the various models of public theology, from a Latin American perspective of theology.